NON-HALAL FOOD SELLER PERCEPTION ON MUSLIM CONSUMER - Muhammad Iqbal; Tri Sasono Hadi; Yunita Nur Afifah (Tasharruf: Journal Economics and Business of Islam, 2020)
Halal food is a significant factor for Muslim consumers because the command to consume halal and haram food is found in the two sources of reference for Muslims, namely the Al-Qur'an and Hadith. The purpose of this study was to see the views of non-Muslim traders in the culinary field regarding halal and haram food in Islam. The view of producers regarding the concept of halal and haram and their application in their trading needs to be known because producer awareness is an essential key in implementing a guarantee system for consumers. Observations made in exploring producers' perceptions or understanding were carrying through interviews with several particular non-halal stall owners engaged in Jogjakarta's food sector. This type of research is qualitative, with a sample of data sources selected by purposive sampling. The researcher takes the sample based on the producer's recognition as the respondent. This study's results reveal that the perception of non-halal food traders only understands Halal partially and ignores other parts so that it tends to benefit Muslim consumers.